The Effect of Tolerance on Balancing Social Relations in Terms of Molana’s Point of View in Masnawi - Kalesara, Ghasem Yaghubinezhad; Mashoor, Parvindokht (Journal of History Culture and Art Research, 2017)
Fresh perceptions and variations in concepts introduced by Molana are among the beautiful effects of Masnavi. It is full of various ploys and mystical paraphrases which imply a new meaning in social issues. In this paper, after a short study of tolerance and its background in Islamic culture and western civilization, it has been discussed socially in Molana’s period. The researchers try to explain tolerance on the basis of two standpoints, by believing that it has a deep influence on balancing human relations. Firstly, we want to know if it is a heavenly or a secular issue since our mystical works talk about an inner source while modern thought is focused on the scientific and experiential roots of wisdom. But in the second step we investigate the relationship between the tolerance and its benefit for the human social rights. Although Molana’s attitude in most of Masnavi’s poems relies on the traditional points of view, this study has realized his mind clarity and vigilance and has come to valuable deductions. He has observed the deepest psychological events and has written them down.